THE ROLE OF DESIGN APPLICATIONS IN DA'WAH CREATIVITY AMONG ISLAMIC COMMUNICATION AND BROADCASTING STUDENTS AT IAI AL-AZIS - Salsa auliya Zachani, Nur; N. Abdurrazaq, Muhammad; Asrof Fitri, Ahmad (Busyro: Jurnal Dakwah dan Komunikasi Islam, 2024)
This research was conducted at the H.M Soeharto building whose target was related to the ability of Islamic Communication and Broadcasting students to use design applications. The second subject matter is, how Islamic Communication and Broadcasting students increase da'wah creativity by using design applications. This research applies qualitative methods that focus on in-depth and detailed observations. Thus, this method can produce a more thorough understanding of the phenomenon or problem being studied. Data were collected through interviews, observations, and documentation with KPI IAI AL-AZIS students. The results of this study show that Islamic Communication and Broadcasting (KPI) students show a good ability to use the Canva design application, which makes it easier for them to make designs. They utilize Canva's features creatively. KPI students can also improve their da'wah creativity through Canva, by following the stages of the creative process and aspects.